Cortico‐limbic connectivity in MAOA‐L carriers is vulnerable to acute tryptophan depletion. Issue 3 (9th December 2016) - Eisner, Patrick; Klasen, Martin; Wolf, Dhana; Zerres, Klaus; Eggermann, Thomas; Eisert, Albrecht; Zvyagintsev, Mikhail; Sarkheil, Pegah; Mathiak, Krystyna A.; Zepf, Florian; Mathiak, Klaus
Abstract: Introduction: A gene–environment interaction between expression genotypes of the monoamine oxidase A (MAOA) and adverse childhood experience increases the risk of antisocial behavior. However, the neural underpinnings of this interaction remain uninvestigated. A cortico‐limbic circuit involving the prefrontal cortex (PFC) and the amygdala is central to the suppression of aggressive impulses and is modulated by serotonin (5‐HT). MAOA genotypes may modulate the vulnerability of this circuit and increase the risk for emotion regulation deficits after specific life events. Acute tryptophan depletion (ATD) challenges 5‐HT regulation and may identify vulnerable neuronal circuits, contributing to the gene–environment interaction. Methods: Functional magnetic resonance imaging measured the resting‐state state activity in 64 healthy males in a double‐blind, placebo‐controlled study. Cortical maps of amygdala correlation identified the impact of ATD and its interaction with low‐ ( MAOA ‐L) and high‐expression variants ( MAOA ‐H) of MAOA on cortico‐limbic connectivity. Results: Across all Regions of Interest (ROIs) exhibiting an ATD effect on cortico‐limbic connectivity, MAOA ‐L carriers were more susceptible to ATD than MAOA ‐H carriers. In particular, the MAOA ‐L group exhibited a larger reduction of amygdala connectivity with the right prefrontal cortex and a larger increase of amygdala connectivity with the insula and dorsal PCC. Conclusion: MAOA ‐L carriers were more susceptable to a central 5‐HT challenge in cortico‐limbic networks. Such vulnerability of the cortical serotonergic system may contribute to the emergence of antisocial behavior after systemic challenges, observed as gene–environment interaction. Hum Brain Mapp 38:1622–1635, 2017 . © 2016 Wiley Periodicals, Inc.